1996
DOI: 10.1074/jbc.271.17.10413
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Active Recombinant α and β Chain-Peptide Complexes of Human Major Histocompatibility Class II Molecules

Abstract: Major histocompatibility (MHC) class II molecules are cell surface heterodimeric (alphabeta) glycoproteins that display processed antigens to T cell receptors (TCRs) of CD4-positive T cells. The present study describes that individual recombinant alpha and beta chains of human MHC class II molecules lacking the transmembrane region (alpha-Tm and beta-Tm) are capable of binding antigenic peptide and that these complexes of chain-peptide are recognized by TCRs to induce antigen-specific apoptosis in restricted T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Soluble recombinant MHC-II molecules in various forms have been developed, from full-length detergent solubilized MHC-II heterodimers (51,52) to various forms of the extracellular a1a2/b1b2 heterodimeric domains (53)(54)(55), and recently the a1 and b1 domains genetically linked into a single polypeptide chain (18 -21, 56). The latter appears to be the smallest structure that retains the peptide binding/ TCR recognition features of MHC-II molecules (33).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble recombinant MHC-II molecules in various forms have been developed, from full-length detergent solubilized MHC-II heterodimers (51,52) to various forms of the extracellular a1a2/b1b2 heterodimeric domains (53)(54)(55), and recently the a1 and b1 domains genetically linked into a single polypeptide chain (18 -21, 56). The latter appears to be the smallest structure that retains the peptide binding/ TCR recognition features of MHC-II molecules (33).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble recombinant MHC class II molecules in various forms have been developed, including full length detergent solubilized MHC class II heterodimers (26, 27), various forms of the extracellular α1α2 and β1β2 heterodimeric domains (2831), and recently the β1 and α1 domains genetically linked into a single polypeptide chain (810, 17, 32). RTL appears to be the smallest structure that retains the peptide binding/TCR recognition features of MHC class II molecules (33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the β2 domain contains a CD4 binding region that co‐ligates CD4 when the α1 and β1 domains with associated antigenic peptide interact with the TCR αβ heterodimer, whereas the α2 domain appears to contribute to ordered oligomerization in T cell activation 15. Complexes of MHC/antigen have been purified as detergent extracts of lymphocyte membranes,16 and as associated recombinant proteins using baculovirus and bacterial expression systems 17–21. These two‐chain, four‐domain molecular complexes, after loading with selected peptide epitopes, have been demonstrated to interact with T cells in an antigen‐specific manner 13, 14, 19, 22–24.…”
Section: Introductionmentioning
confidence: 99%
“…These two‐chain, four‐domain molecular complexes, after loading with selected peptide epitopes, have been demonstrated to interact with T cells in an antigen‐specific manner 13, 14, 19, 22–24. In some cases, in the absence of co‐stimulation, these complexes induced antigen‐specific apoptosis rather than anergy 20. Desbarats et al showed that cross‐linking CD4 can enhance Fas (CD95) expression and activate apoptotic cell death 25.…”
Section: Introductionmentioning
confidence: 99%